Diversity of mosquito species ovipositing in different zones of light intensity within limestone caves in Thailand - Thavin Bodharamik (2019)
Copyright © 2018 by The American Mosquito Control Association, Inc. Climate change and human activity affect the geographical and annual distribution and population abundance of mosquitoes. As natural habitats are reduced, it is hypothesized that mosquitoes may seek refuge in more stable environments such as cave habitats. Therefore, we explored the species diversity of mosquitoes exploiting cave habitats in Thailand. Ten species belonging to 4 genera were collected, of which none were considered to be true cave-dwelling species (Troglobiont). The known cavernicolous species, Aedes cavaticus, was observed to oviposit outside of the cave and therefore should be categorized as a subtroglophilic species. Other species were also oviposited inside the cave but should be regarded as trogloxenic species. There was no clear association between environmental factors and mosquito abundance inside the 4 limestone caves, except for Ae. cavaticus, which was positively correlated with rainfall. This study indicates that different biotic or abiotic factors may be involved in mosquito oviposition site selection inside caves.